2017
DOI: 10.1128/cmr.00046-17
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BAFF System Molecules in Host Response to Pathogens

Abstract: The two ligands B cell-activating factor of the tumor necrosis factor family (BAFF) and a proliferation-inducing ligand (APRIL) and the three receptors BAFF receptor (BAFF-R), transmembrane activator and calcium-modulating cyclophilin ligand interactor (TACI), and B cell maturation antigen (BCMA) are members of the "BAFF system molecules." BAFF system molecules are primarily involved in B cell homeostasis. The relevance of BAFF system molecules in host responses to microbial assaults has been investigated in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 196 publications
(244 reference statements)
3
80
0
Order By: Relevance
“…21,22 B cell-activating factor (BAFF) and proliferation-inducing ligand (APRIL) have been implicated in B-cell stimulation by dengue-infected CD14 + CD16 + monocytes, and, like dengue infection, R848 stimulates BAFF and APRIL production by monocytes. 21 BAFF and APRIL bind to BAFF family receptors that are expressed almost exclusively by B cells, 23 including BAFF-R and transmembrane activator and calciummodulator interactor TACI, 24 as well as B-cell maturation antigen (BCMA), which is mainly expressed by bone marrow plasma cells. 25 Therefore, we examined whether BAFF-R and TACI expression changes after B-cell stimulation with R848, and whether these changes are altered by the presence of monocytes.…”
Section: Cytokine Production In Naive and Memory B-cell Stimulation Cmentioning
confidence: 99%
“…21,22 B cell-activating factor (BAFF) and proliferation-inducing ligand (APRIL) have been implicated in B-cell stimulation by dengue-infected CD14 + CD16 + monocytes, and, like dengue infection, R848 stimulates BAFF and APRIL production by monocytes. 21 BAFF and APRIL bind to BAFF family receptors that are expressed almost exclusively by B cells, 23 including BAFF-R and transmembrane activator and calciummodulator interactor TACI, 24 as well as B-cell maturation antigen (BCMA), which is mainly expressed by bone marrow plasma cells. 25 Therefore, we examined whether BAFF-R and TACI expression changes after B-cell stimulation with R848, and whether these changes are altered by the presence of monocytes.…”
Section: Cytokine Production In Naive and Memory B-cell Stimulation Cmentioning
confidence: 99%
“…In this study, we demonstrated that bacterial lipoproteins are major bacterial products with a strong BAFF-inducing capacity in DCs and also confirmed that indirect B-cell activating capacity of bacterial lipoproteins via BAFF production is beyond its direct effect. On the other hand, previous data from clinical and in vivo studies revealed increased expression levels of BAFF during bacterial infections by Mycoplasma pneumoniae , Mycobacterium tuberculosis , and Pseudomonas aeruginosa ( 68 ). In addition, increased levels of serum BAFF appear to correlate with disease severity in bacterial infectious diseases, such as tuberculosis ( 69 ).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, increased levels of serum BAFF appear to correlate with disease severity in bacterial infectious diseases, such as tuberculosis ( 69 ). Since BAFF can promote inflammatory responses by inducing excessive Th1 and Th17 responses ( 16 , 68 ), BAFF production by bacterial lipoprotein might be closely related with progression and persistence of the bacterial infectious diseases. Moreover, bacterial lipoproteins have a potency to produce cytokines having BAFF-inducing ability, such as TNF-α and IL-10 ( 70 , 71 ), leading to synergistically enhanced BAFF production in DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Since their discovery in the mid‐1960s, B lymphocytes were mainly known for their ability to produce antibodies . The B‐cell‐derived antibody response has been reported to be critical to protect against microbial infections or mediate autoimmune diseases . Although the role of B cells in tumors is still conflicting and controversial, due to their antibody‐producing capacity, tumor‐infiltrating B cells are recognized as anti‐tumor immune components …”
Section: Introductionmentioning
confidence: 99%